Manufacturing method of glass through hole capable of realizing high aspect ratio
Through pretreatment of the glass substrate and multi-step laser irradiation, acid-base corrosion and metal protective layer treatment, the problem of insufficient controllability of high aspect ratio and pore diameter in the prior art is solved, and efficient and controllable glass through-hole formation is achieved, which is suitable for high-density interconnection applications.
Patent Information
- Application Number
- CN202411969057.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
The existing glass through-hole technology has encountered bottlenecks in achieving high aspect ratio and controllability of pore size, resulting in a decrease in the depth of pores, a larger pore size, and an increase in the distribution of corrosion ion and exchange difficulty, affecting high-density interconnection applications.
By pretreating the glass substrate, a modified region is formed using a first laser, and a first blind hole with a depth of 100 μm or more is formed by corrosion by the first acid solution or the first alkali solution. Subsequently, the metal protective layer is deposited and oxidized by a second laser, followed by gradual corrosion of the second acid solution and the second alkali solution to form the second blind hole, and finally the protective layer is removed by the metal etching solution, and the above steps are repeated until the through hole is formed.
A glass through-hole with high aspect ratio and controllable aperture is realized, which avoids corrosion and thinning in the unmodified areas of the glass substrate and improves the controllability and efficiency of the pore type.
Smart Images

Figure CN119822645A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chip packaging, and in particular to a method for manufacturing a through-glass hole capable of achieving a high aspect ratio. Background Art
[0002] With the booming development of the semiconductor industry, the demand for high integration and high performance of electronic devices is increasing. Traditional two-dimensional packaging technology is difficult to meet the further development requirements of electronic devices due to its physical space limitations. Therefore, three-dimensional integration and advanced packaging technology (3D-stacking and Advanced Packaging) were proposed. This technology greatly improves the integration and performance of devices by introducing vertical through-hole structures to achieve electrical interconnection between multi-layer substrates. Glass through-hole structures are glass substrates with a large number of holes. These holes provide vertical electrical connections through the glass substrate. They are called glass through-hole structures (TGV).
[0003] To provide through glass vias (TGVs), a LIAE process is used. The LIAE process involves laser irradiation of the glass. Laser irradiation changes the microstructure of the glass and makes the irradiated areas more susceptible to etching chemistry. After laser irradiation, wet etching is performed through the openings. This LIAE process is generally suitable for TGV fabrication with relatively low aspect ratios (e.g., height:width).
[0004] However, the current through-glass via technology has encountered many bottlenecks in achieving ultra-high aspect ratios. First, the power of existing laser equipment is not enough to completely change the material properties of the punching area of the glass substrate, resulting in a low degree of modification, a long punching time, and a low subsequent chemical etching rate. Secondly, since the etching solution can also etch the unmodified area, wet etching has isotropic physical points, which will make the glass substrate thinner, resulting in a decrease in hole depth; at the same time, in order to increase the etching depth of the hole, it is necessary to increase the etching time, so the aperture of the through hole will inevitably be larger. At the same time, as the aspect ratio continues to increase, the distribution and exchange of corrosion ions in the hole are becoming more and more difficult, and the aperture and shape of the through hole are also more difficult to control. These factors limit the realization of high aspect ratio through holes and hinder their application in the field of high-density interconnection.
[0005] Therefore, there is an urgent need for a method for forming a through-glass hole with a high aspect ratio, controllable aperture, and good hole shape to meet the current industry's demand for high integration and high performance of electronic devices. Summary of the invention
[0006] The object of the present invention is to provide a method for manufacturing a through-glass via with a high aspect ratio. The through-glass via with a high aspect ratio and controllable aperture can be obtained by the manufacturing method of the present application.
[0007] To achieve the above object, the present invention provides a method for manufacturing a through-glass via with a high aspect ratio, comprising the steps of:
[0008] S1 pre-treats the glass substrate;
[0009] S2 uses a first laser to irradiate the preset through-hole positions on the upper and lower surfaces of the glass substrate to form a modified area;
[0010] S3 cleans and dries the glass substrate;
[0011] S4: using a first acid solution or a first alkali solution to perform a first etching on the modified area to form a first blind hole, wherein the first blind hole has a preset through hole diameter and a depth of 100 μm or more;
[0012] S5 cleans and dries the glass substrate;
[0013] S6 forms a metal protective layer on the upper and lower surfaces of the glass substrate by a deposition process, wherein the thickness of the metal protective layer is greater than 0.1 μm, and the metal protective layer includes a titanium layer formed on the surface of the glass substrate and an inert metal layer formed on the surface of the titanium layer;
[0014] S7 uses a second laser to oxidize and ablate the metal protection layer deposited at the bottom of the blind hole to form a metal oxide layer;
[0015] S8 sequentially uses a second acid solution and a second alkali solution to perform a second etching on the first blind hole to form a second blind hole;
[0016] S9 uses metal etching solution to remove the metal protective layer on the upper and lower surfaces of the glass substrate;
[0017] S10 cleans and dries the glass substrate;
[0018] S11 repeats S6 to S10 until the glass in the second blind hole is removed to form a through hole.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects:
[0020] (1) The present invention firstly performs a first etching on the modified area to obtain a first blind hole with a depth of 100 μm or more and a preset through hole diameter, and then uses a deposition process to form a metal protective layer with a thickness of not less than 0.1 μm on the upper and lower surfaces of the glass substrate. In this way, a protective barrier can be formed on the surface of the glass substrate and the inner wall of the blind hole to prevent the unmodified area of the glass substrate from becoming thinner due to corrosion, thereby reducing the aspect ratio of the glass through hole. At the same time, the aforementioned setting of the blind hole depth and the thickness of the metal protective layer can expose the modified area (i.e., the first blind hole), which is more conducive to the subsequent second laser oxidation ablation and second etching steps.
[0021] (2) Since the inert metal is inert in the acid solution, the present invention deposits an inert metal layer on the surface of the glass substrate to form a protective barrier for the glass substrate, and further deposits a titanium layer between the inert metal layer and the glass substrate to effectively improve the adhesion between the inert metal layer and the glass substrate. This can effectively avoid the situation in which the inert metal layer falls off from the surface of the glass substrate during the subsequent second etching process, resulting in corrosion and thinning of the unmodified area and thus reducing the aspect ratio of the glass through hole.
[0022] (3) The present invention uses a second laser to perform oxidation ablation on the bottom of the first blind hole. During the laser ablation process, the metal in the metal oxide layer at the bottom of the first blind hole combines with oxygen in the air to form a metal oxide layer. During the second etching process, since there is still a metal protective layer on the surface of the glass substrate and the inner wall of the first blind hole, and the properties of the inert metal element are less active than the properties of the metal oxide, it can effectively prevent the inner wall of the first blind hole from being corroded and further increasing the aperture, thereby making the aperture controllable. The present invention uses acid solution first and then alkali solution in the second etching because acid solution decomposes the metal oxide layer faster, while alkali solution decomposes and corrodes the glass faster. Such a setting can further improve the corrosion efficiency of the second etching and effectively reduce the corrosion of the non-modified area of the glass substrate, further reducing the phenomenon that the aspect ratio of the glass through hole is reduced due to the thinning of the non-modified area.
[0023] In summary, the preparation method of the present invention can obtain a through-glass hole with a high aspect ratio and controllable hole shape.
[0024] As a preferred technical solution, the pretreatment of the present invention includes placing the glass substrate in a cleaning solution for ultrasonic cleaning and then drying.
[0025] As a preferred technical solution, the cleaning solution of the present invention includes deionized water, ethanol and acetone.
[0026] As a preferred technical solution, the first laser and the second laser of the present invention are independently selected from femtosecond lasers or picosecond lasers.
[0027] As a preferred technical solution, the first laser of the present invention is a femtosecond laser, and the working parameters of the femtosecond laser are: the laser focal length is 0.1mm-0.3mm, the laser irradiation power is 25%-55% of the maximum power of the femtosecond laser, the laser scanning speed is 2mm / s-5mm / s, and the laser processing acceleration is 10mm / s 3 ~50mm / s 3 .
[0028] As a preferred technical solution, the second laser of the present invention is a femtosecond laser, and the working parameters of the femtosecond laser are: the laser focal length is 3.6mm-3.9mm, the laser irradiation power is 80%-100% of the maximum power of the femtosecond laser, the laser scanning speed is 18mm / s-25mm / s, and the laser processing acceleration is 180mm / s 3 ~220mm / s 3 .
[0029] As a preferred technical solution, the acids in the first acid solution and the second acid solution of the present invention are independently selected from at least one of hydrochloric acid, sulfuric acid and hydrofluoric acid.
[0030] As a preferred technical solution, the alkali in the first alkali solution and the second alkali solution of the present invention is independently selected from at least one of potassium hydroxide and sodium hydroxide.
[0031] As a preferred technical solution, the second etching of the present invention includes firstly treating the metal oxide layer with a second acid solution to expose the glass substrate at the bottom of the first blind hole, and then etching the glass substrate at the bottom of the first blind hole with a second alkali solution.
[0032] As a preferred technical solution, the content of alkali in the second alkali solution of the present invention is 40% to 50%.
[0033] As a preferred technical solution, the corrosion temperature in the second alkali solution of the present invention is 60°C to 85°C.
[0034] As a preferred technical solution, the deposition process of the present invention is selected from at least one of chemical plating, atomic layer deposition and physical vapor deposition.
[0035] As a preferred technical solution, the thickness of the titanium layer of the present invention is 0.01 μm to 0.3 μm, and the thickness of the inert metal layer is 0.1 μm to 4 μm.
[0036] As a preferred technical solution, the inert metal layer of the present invention is a copper layer, a nickel layer or a gold layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of a through-glass via prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention provides a method for manufacturing a through-glass hole capable of achieving a high aspect ratio, comprising the steps of:
[0039] S1 pre-treats the glass substrate;
[0040] S2 uses a first laser to irradiate the preset through-hole positions on the upper and lower surfaces of the glass substrate to form a modified area;
[0041] S3 cleans and dries the glass substrate;
[0042] S4: using a first acid solution or a first alkaline solution to perform a first etching on the modified area to form a first blind hole;
[0043] S5 cleans and dries the glass substrate;
[0044] S6 uses a deposition process to form a metal protective layer on the upper and lower surfaces of the glass substrate;
[0045] S7 uses a second laser to oxidize and ablate the metal protection layer deposited at the bottom of the blind hole to form a metal oxide layer;
[0046] S8 sequentially uses a second acid solution and a second alkali solution to perform a second etching on the first blind hole to form a second blind hole.
[0047] S9 uses metal etching solution to remove the metal protective layer on the upper and lower surfaces of the glass substrate;
[0048] S10 cleans and dries the glass substrate;
[0049] S11 repeats S6 to S10 until the glass in the second blind hole is removed to form a through hole.
[0050] Specifically, in S1, the pretreatment includes placing the glass substrate in a cleaning solution for ultrasonic cleaning and then drying. The cleaning solution includes deionized water, ethanol and acetone. Specifically, the mass ratio of deionized water, ethanol and acetone may be 5:3:2, but is not limited thereto. The working power of the ultrasonic machine may be 20W to 150W. As an example, the working power of the ultrasonic machine may be, but is not limited to, 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, and the ultrasonic cleaning time is 10min to 15min. As an example, the ultrasonic cleaning time may be, but is not limited to, 10min, 11min, 12min, 13min, 14min, 15min. Drying can be hot air drying, and the drying temperature is 80°C to 120°C. As an example, the drying temperature can be, but is not limited to, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C. The present invention has no particular limitation on the drying time, and it is sufficient to dry until the surface of the glass substrate is visually free of water. The present invention can effectively remove dust and organic pollutants on the surface of the glass substrate by pre-treating the glass substrate under the above conditions, which is conducive to subsequent laser modification and etching pore forming treatment.
[0051] In S2, the first laser is selected from a femtosecond laser or a picosecond laser. Preferably, the first laser is a femtosecond laser. The working parameters of the femtosecond laser are that the laser focal length is 0.1mm to 0.3mm. Specifically, the laser focal length can be, but is not limited to, 0.1mm, 0.2mm, and 0.3mm. The laser irradiation power is 25% to 55% of the maximum power of the femtosecond laser. Specifically, the laser irradiation power is 25%, 30%, 35%, 40%, 45%, 50%, and 55% of the maximum power of the femtosecond laser, but is not limited thereto. The laser scanning speed is 2mm / s to 5mm / s. Specifically, the laser scanning speed is 2mm / s, 3mm / s, 4mm / s, and 5mm / s, but is not limited thereto. The laser processing acceleration is 10mm / s 3 ~50mm / s 3 Specifically, the laser processing acceleration can be but is not limited to 10 mm / s 3 , 20mm / s 3 、30mm / s 3 , 40mm / s 3 , 50mm / s 3 A femtosecond laser is used as the laser light source, and the laser focal length, irradiation power, scanning speed, and processing acceleration of the femtosecond laser are controlled within the above ranges. Due to its extremely short pulse time and concentrated energy, the surface of the glass substrate can be instantly heated up and then cooled, thereby reducing the influence of thermal effects, achieving precise control of the size of the preset position of the through hole, and ensuring the smoothness and integrity of the edge of the preset position of the through hole of the present invention.
[0052] In S3, after the modified area is formed, the glass substrate is also cleaned and dried. Specifically, the cleaning includes placing the glass substrate in a cleaning tank of an ultrasonic cleaning device, using cleaning liquid, ethanol and deionized water as cleaning media, and performing ultrasonic cleaning. The mass ratio of the cleaning liquid, ethanol and deionized water can be 0.05-0.2:0.1-0.2:1. Specifically, the mass ratio of the cleaning liquid, ethanol and deionized water can be but is not limited to 0.05:0.1:1, 0.1:0.1:1, 0.2:0.1:1, 0.05:0.2:1, 0.1:0.2:1, 0.2:0.2:1. The cleaning liquid is a cleaning liquid commonly used in the field of glass through-hole production, and its specific model is not limited here. The working power of the ultrasonic machine can be 50W to 2000W, specifically, the working power of the ultrasonic machine can be but not limited to 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, 180W, 200W, the time of ultrasonic cleaning is 15min to 30min, specifically, the time of ultrasonic cleaning can be but not limited to 15min, 16min, 17min, 18min, 19min, 20min, 22min, 24min, 26min, 28min, 30min. Drying can be hot air drying, and the drying temperature is 80℃ to 120℃, specifically, the drying temperature can be but not limited to 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃. By cleaning the glass substrate under the above conditions, impurities, dirt and contamination caused by laser-induced modification on the surface of the glass substrate and possible contamination during processing can be effectively removed, so that the etching process is more uniform and the roughness of the side wall of the glass through hole is reduced.
[0053] In S4, the acid in the first acid solution is selected from at least one of hydrochloric acid, sulfuric acid and hydrofluoric acid. The alkali in the first alkali solution is selected from at least one of sodium hydroxide and potassium hydroxide. The first acid solution or the first alkali solution is used to perform the first corrosion on the modified area. Since the modified area formed after the first laser irradiation is easier to be corroded and decomposed than the glass in the area not irradiated by the laser, the first blind hole is formed at the preset through hole position. When the first blind hole reaches the preset through hole diameter and the depth is 100μm or more, the corrosion is stopped to avoid the situation where the glass in the unmodified area is also corroded and thinned over a long period of time, thereby affecting the aspect ratio of the glass through hole. The concentration of the first acid solution is 3% to 15%. Specifically, the concentration of the first acid solution can be but is not limited to 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Preferably, the concentration of the first acid solution is 3% to 6%. The content of alkali in the first alkali solution is 40% to 50%. Specifically, the content of alkali in the first alkali solution is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, and 50%.
[0054] In S5, after forming the first blind hole, the glass substrate is also cleaned and dried. Specifically, the cleaning includes placing the glass substrate in a cleaning tank of an ultrasonic cleaning device, using deionized water as a cleaning medium, and performing ultrasonic cleaning to effectively remove the residual corrosive liquid inside and on the surface of the blind hole. After cleaning, hot air is used for drying to remove moisture from the surface of the glass substrate and the blind hole. The working power of the ultrasonic machine can be 20W to 150W. As an example, the working power of the ultrasonic machine can be but not limited to 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, and the time for ultrasonic cleaning is 10min to 15min. As an example, the time for ultrasonic cleaning can be but not limited to 10min, 11min, 12min, 13min, 14min, 15min. The drying temperature is 80°C to 120°C. As an example, the drying temperature can be but is not limited to 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C.
[0055] In S6, the deposition process is selected from at least one of chemical plating, atomic layer deposition and physical vapor deposition. Depositing an inert metal layer on the surface of the glass substrate can effectively prevent the corrosion of the unmodified area of the glass substrate by the corrosive liquid in the subsequent etching and hole forming process. However, the adhesion between the inert metal and the glass substrate is poor. By depositing a titanium layer between the inert metal layer and the glass substrate, the adhesion between the inert metal and the glass substrate can be effectively improved, thereby effectively avoiding the corrosion of the unmodified area due to the fall-off of the inert metal layer on the surface of the glass substrate during the subsequent etching and processing, thereby affecting the aspect ratio. Specifically, firstly, atomic layer deposition or physical vapor deposition is used to form a titanium layer on the upper and lower surfaces of the glass substrate. When titanium is deposited on the surface of the glass substrate by the above method, a Ti-O-Si bond can be formed, thereby improving the adhesion of titanium to the surface of the glass substrate. Then, an inert metal layer is deposited on the surface of the titanium layer, which can improve the bonding strength between the inert metal layer and the titanium layer, thereby improving the bonding strength between the inert metal layer and the glass substrate. It should be noted that the chemical plating, atomic layer deposition and physical vapor deposition of the present invention are existing processes, and the present invention does not limit their specific process conditions. The above processes can be used to sequentially form a titanium layer and an inert metal layer on the surface of a glass substrate.
[0056] The thickness of the metal protective layer is 0.1 μm or more, and the thickness of the titanium layer is 0.01 μm to 0.3 μm. Specifically, the thickness of the titanium layer can be, but not limited to, 0.01 μm, 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, and 0.3 μm. The thickness of the inert metal layer is 0.1 μm to 4 μm. Specifically, the thickness of the inert metal layer can be, but not limited to, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, and 4 μm. The inert metal layer can be a copper layer, a nickel layer, or a gold layer. The copper layer, the nickel layer, and the gold layer are all inert in the acid solution at room temperature. The use of an inert metal layer to protect the glass substrate can effectively avoid the corrosion and decomposition of the unmodified area in the glass substrate in the subsequent second etching process, and avoid the aspect ratio of the glass substrate being affected by the corrosion and thinning.
[0057] In S7, the second laser can be selected from a picosecond laser or a femtosecond laser. Specifically, the second laser is selected from a femtosecond laser. The working parameters of the femtosecond laser are: the laser focal length is 3.6mm to 3.9mm, specifically, the laser focal length can be but not limited to 3.6mm, 3.7mm, 3.8mm, 3.9mm. The laser irradiation power is 80% to 100% of the maximum power of the femtosecond laser, and the laser scanning speed is 18mm / s to 25mm / s. Specifically, the laser scanning speed can be but not limited to 18mm / s, 19mm / s, 20mm / s, 21mm / s, 22mm / s, 23mm / s, 24mm / s, 25mm / s. The laser processing acceleration is 180mm / s3 ~220mm / s 3 Specifically, the laser processing acceleration can be but is not limited to 180 mm / s 3 、190mm / s 3 , 200mm / s 3 , 210mm / s 3 , 220mm / s 3 The second laser is used to irradiate the metal protective layer at the bottom of the blind hole. Under the above working conditions, the metal in the metal protective layer combines with the oxygen in the air to form a metal oxide layer, which is easier to be destroyed and decomposed in the acid solution in the subsequent second etching than the metal element, thereby exposing the glass substrate at the bottom of the blind hole, and then using alkaline solution for the subsequent second etching work.
[0058] In S8, the second etching includes first using a second acid solution to treat the metal oxide layer to expose the glass substrate at the bottom of the first blind hole, and then using a second alkali solution to etch the glass substrate at the bottom of the first blind hole. The present invention first uses the second acid solution for treatment because the acid solution can effectively remove the metal oxide at the bottom of the blind hole and thus expose the glass substrate at the bottom of the blind hole, and then uses the alkali solution for treatment because although the alkali solution also has a certain corrosion effect on the metal protective layer, its corrosion effect on the glass substrate is stronger than that of the acid solution.
[0059] The acid in the second acid solution is selected from at least one of hydrochloric acid, sulfuric acid and hydrofluoric acid. The alkali in the second alkali solution is selected from at least one of sodium hydroxide and potassium hydroxide. The concentration of the second acid solution is 3% to 15%. Specifically, the concentration of the second acid solution can be but not limited to 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Preferably, the concentration of the second acid solution is 3% to 6%. The content of alkali in the second alkali solution is 40% to 50%. Specifically, the content of alkali in the alkali solution can be but not limited to 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%. The corrosion temperature in the second alkali solution is 60°C to 85°C. Specifically, the corrosion temperature in the second alkali solution can be but not limited to 60°C, 65°C, 70°C, 75°C, 80°C.
[0060] It should be noted that the first acid solution and the second acid solution of the present invention may be the same or different, and the first alkali solution and the second alkali solution of the present invention may be the same or different.
[0061] In S9, the metal etching solution is a metal etching solution commonly used in the art, and its specific model is not limited here.
[0062] In S10, the cleaning includes placing the glass substrate in a cleaning tank of an ultrasonic cleaning device, using a cleaning liquid as a cleaning medium, and performing ultrasonic cleaning to effectively remove the residual corrosive liquid inside and on the surface of the blind hole. After the cleaning is completed, hot air is used for drying to remove the moisture on the surface of the glass substrate and in the blind hole. The cleaning liquid is a cleaning liquid commonly used in the field of glass pupil processing, and the present invention does not limit its specific model. The working power of the ultrasonic machine can be 20W to 150W. As an example, the working power of the ultrasonic machine can be but not limited to 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, and the time of ultrasonic cleaning is 10min to 15min. As an example, the time of ultrasonic cleaning can be but not limited to 10min, 11min, 12min, 13min, 14min, 15min. The drying temperature is 80°C to 120°C. As an example, the drying temperature can be but is not limited to 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C.
[0063] In S11 , the operation process of S6 to S10 may be repeated to achieve through-hole etching with a higher aspect ratio.
[0064] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0065] Example 1
[0066] S1: placing the glass substrate in a cleaning solution for ultrasonic cleaning and then drying it in hot air, wherein the cleaning solution is a mixed solution of deionized water, ethanol and acetone in a mass ratio of 5:3:2, the working power of the ultrasonic machine is 100W, the ultrasonic cleaning time is 10min, and the drying temperature is 100°C;
[0067] S2 uses a femtosecond laser to irradiate the preset through-hole positions on the upper and lower surfaces of the glass substrate to form a modified area. The working parameters of the femtosecond laser are: laser focal length of 0.2mm, laser irradiation power of 40% of the maximum power of the femtosecond laser, laser scanning speed of 4mm / s, laser processing acceleration of 30mm / s 3 ;
[0068] S3 puts the glass substrate into the cleaning tank of the ultrasonic cleaning equipment, uses cleaning liquid, ethanol and deionized water as cleaning media, performs ultrasonic cleaning and then dries. The working power of the ultrasonic machine is 100W, the cleaning time is 25min, and the drying temperature is 100°C.
[0069] S4: using 5% hydrofluoric acid to perform a first etching on the modified area to form a first blind hole, and stopping the etching when the first blind hole reaches a preset through hole diameter and a depth of 110 μm;
[0070] S5 puts the glass substrate into a cleaning tank of an ultrasonic cleaning device, uses deionized water as a cleaning medium, performs ultrasonic cleaning, and then dries. The working power of the ultrasonic machine is 80W, the cleaning time is 12 minutes, and the drying temperature is 100°C.
[0071] S6 uses physical vapor deposition to form a metal protective layer on the upper and lower surfaces of the glass substrate, the metal protective layer includes a titanium layer formed on the surface of the glass substrate and a copper layer formed on the surface of the titanium layer, wherein the thickness of the titanium layer is 0.2 μm and the thickness of the copper layer is 3 μm;
[0072] S7 uses a femtosecond laser to oxidize and ablate the metal protective layer deposited at the bottom of the blind hole to form a metal oxide layer. The working parameters of the femtosecond laser are: laser focal length is 3.8mm, laser irradiation power is 90% of the maximum power of the femtosecond laser, laser scanning speed is 20mm / s, and laser processing acceleration is 200mm / s. 3 , the laser pulse is 2;
[0073] S8: First, 5% hydrofluoric acid is used to treat the metal oxide layer to expose the glass substrate at the bottom of the first blind hole, and the residual hydrofluoric acid on the glass substrate is cleaned with deionized water, and then a 40% potassium hydroxide solution is used to etch the glass substrate at the bottom of the first blind hole to form a second blind hole. The temperature of the glass substrate in the potassium hydroxide is 70°C;
[0074] S9 uses metal etching solution to remove the metal protective layer on the upper and lower surfaces of the glass substrate;
[0075] S10: placing the glass substrate into a cleaning tank of an ultrasonic cleaning device, using a cleaning liquid as a cleaning medium, ultrasonically cleaning and then drying. The working power of the ultrasonic machine is 80W, the cleaning time is 12 minutes, and the drying temperature is 100°C.
[0076] S11 repeats S6 to S10 until the glass in the second blind hole is removed to form a through hole.
[0077] like Figure 1 As shown, observation using a Keyence VK-3000 microscope revealed that the depth of the through-glass hole prepared in this embodiment was 1462.7 μm, the aperture was 31.79 μm, the aspect ratio of the through-glass hole was 46:1, and the morphology was good.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for producing a through-glass hole having a high aspect ratio, characterized in that: include: S1 pre-treats the glass substrate; S2: using a first laser to irradiate the preset through-hole positions on the upper and lower surfaces of the glass substrate to form a modified area; S3: cleaning and drying the glass substrate; S4: using a first acid solution or a first alkali solution to perform a first etching on the modified area to form a first blind hole, wherein the first blind hole has a preset through hole diameter and a depth of 100 μm or more; S5: cleaning and drying the glass substrate; S6: forming a metal protective layer on the upper and lower surfaces of the glass substrate by a deposition process, wherein the thickness of the metal protective layer is greater than 0.1 μm, and the metal protective layer includes a titanium layer formed on the surface of the glass substrate and an inert metal layer formed on the surface of the titanium layer; S7: using a second laser to oxidize and ablate the metal protection layer deposited at the bottom of the blind hole to form a metal oxide layer; S8 sequentially uses a second acid solution and a second alkali solution to perform a second etching on the first blind hole to form a second blind hole; S9: using a metal etching solution to remove the metal protective layer on the upper and lower surfaces of the glass substrate; S10: cleaning and drying the glass substrate; S11 repeats S6 to S10 until the glass in the second blind hole is removed to form a through hole.
2. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The pretreatment comprises placing the glass substrate in a cleaning solution for ultrasonic cleaning and then drying, wherein the cleaning solution comprises deionized water, ethanol and acetone.
3. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The first laser and the second laser are each independently selected from a femtosecond laser or a picosecond laser.
4. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 3, characterized in that: The first laser is a femtosecond laser, and the working parameters of the femtosecond laser are: laser focal length is 0.1mm-0.3mm, laser irradiation power is 25%-55% of the maximum power of the femtosecond laser, laser scanning speed is 2mm / s-5mm / s, and laser processing acceleration is 10mm / s 3 ~50mm / s 3 .
5. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 3, characterized in that: The second laser is a femtosecond laser, and the working parameters of the femtosecond laser are: laser focal length is 3.6mm-3.9mm, laser irradiation power is 80%-100% of the maximum power of the femtosecond laser, laser scanning speed is 18mm / s-25mm / s, and laser processing acceleration is 180mm / s 3 ~220mm / s 3 .
6. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The acid in the first acid solution and the second acid solution is independently selected from at least one of hydrochloric acid, sulfuric acid and hydrofluoric acid, and the alkali in the first alkali solution and the second alkali solution is independently selected from at least one of potassium hydroxide and sodium hydroxide.
7. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The second etching comprises firstly using the second acid solution to treat the metal oxide layer to expose the glass substrate at the bottom of the first blind hole, and then using the second alkali solution to etch the glass substrate at the bottom of the first blind hole.
8. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 6, characterized in that: The alkali content in the second alkali solution is 40% to 50%, and the corrosion temperature in the second alkali solution is 60° C. to 85° C.
9. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The deposition process is selected from at least one of chemical plating, atomic layer deposition and physical vapor deposition.
10. The method for manufacturing a through-glass via capable of achieving a high aspect ratio according to claim 1, characterized in that: The thickness of the titanium layer is 0.01 μm to 0.3 μm, the thickness of the inert metal layer is 0.1 μm to 4 μm, and the inert metal layer is a copper layer, a nickel layer or a gold layer.